Oral Immunotherapy in Food Allergy: A Critical Pediatric Perspective - Akarsu, Aysegul; Brindisi, Giulia; Fiocchi, Alessandro; Zicari, Anna Maria; Arasi, Stefania (Frontiers in Pediatrics, 2022)
There is evidence that in children with persistent IgE-mediated food allergy (FA) to cow's milk, hen's egg, and peanut, oral allergen-specific immunotherapy (OIT) may increase the reaction threshold to the culprit food allergen(s). OIT may protect patients from the occurrence of severe reactions in case of accidental ingestion of the culprit food during treatment. Notwithstanding, many gaps are still unsolved, including safety issues, identification of predictive biomarkers, and post-desensitization efficacy. In this perspective, the use of omalizumab (Anti-IgE monoclonal antibody) has been proposed as an adjunctive treatment to OIT in order to reduce the risk of allergic reactions related to OIT. This review aims to summarize the current evidence and unmet needs on OIT in children with FA to enhance the development of longitudinal, prospective, and well-designed studies able to fill the current gaps soon.